IMPLEMETASI HUKUM KELUARGA ISLAM PADA UNDANG-UNDANG PERKAWINAN DI INDONESIA MENGENAI HAK MEMILIH PASANGAN BAGI PEREMPUAN - Arif Sugitanata; Suud Sarim Karimullah (Jurnal Studi Gender dan Anak, 2023)
This paper discusses the implementation of Islamic family law in Indonesia's marriage law regarding the right to choose a partner for women with the main problem explaining how the interrelationships of the values ​​of Islamic family law are absorbed in Indonesian laws. Utilizing a literature study whose primary data sources come from books, journals and statutes, this research finds that Indonesia, as a country known for its Muslim majority and having many ethnicities and cultures, also adopts the principles of equality in Islam implemented in Marriage Law No. 1 of 1974 is included in the realm of choosing a mate for women. As stipulated in UUP No. 1 of 1974 concerning the conditions for marriage regulated in Article 6 Paragraph 1, namely that there must be the consent of the bride, meaning that the woman is willing to be married by a man who wants to marry her without any coercion. What is contained in Article 6 Paragraph 1 UUP No. 1 of 1974 is in line with the mission of Islam, namely the principle of equality for women. This aims to build a happy and eternal household and of course in line with human rights.